# SOLUTION: I need to completely factor the trinomial x^2+2x-35. I've tried to figure it out myself and every time I get a different answer. Then I tried a solver and it said it couldn't be f

Algebra ->  Algebra  -> Polynomials-and-rational-expressions -> SOLUTION: I need to completely factor the trinomial x^2+2x-35. I've tried to figure it out myself and every time I get a different answer. Then I tried a solver and it said it couldn't be f      Log On

 Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help! Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations!

 Algebra: Polynomials, rational expressions and equations Solvers Lessons Answers archive Quiz In Depth

Question 452947: I need to completely factor the trinomial x^2+2x-35.
I've tried to figure it out myself and every time I get a different answer. Then I tried a solver and it said it couldn't be factored and that's not even one of the choices in my homework. It asks for an answer or whether the polynomial is prime. I'm so confused. Can someone help?

You can put this solution on YOUR website!

Looking at the expression , we can see that the first coefficient is , the second coefficient is , and the last term is .

Now multiply the first coefficient by the last term to get .

Now the question is: what two whole numbers multiply to (the previous product) and add to the second coefficient ?

To find these two numbers, we need to list all of the factors of (the previous product).

Factors of :
1,5,7,35
-1,-5,-7,-35

Note: list the negative of each factor. This will allow us to find all possible combinations.

These factors pair up and multiply to .
1*(-35) = -35
5*(-7) = -35
(-1)*(35) = -35
(-5)*(7) = -35

Now let's add up each pair of factors to see if one pair adds to the middle coefficient :

First NumberSecond NumberSum
1-351+(-35)=-34
5-75+(-7)=-2
-135-1+35=34
-57-5+7=2

From the table, we can see that the two numbers and add to (the middle coefficient).

So the two numbers and both multiply to and add to

Now replace the middle term with . Remember, and add to . So this shows us that .

Replace the second term with .

Group the terms into two pairs.

Factor out the GCF from the first group.

Factor out from the second group. The goal of this step is to make the terms in the second parenthesis equal to the terms in the first parenthesis.

Combine like terms. Or factor out the common term

===============================================================